(untitled) (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2021)
Nudibranchs are marine invertebrates from the mollusc phylum of the gastropod class subclass Opisthobranchiata. Nudribanch has many benefits because of its compound content, has the beauty of attractive colors as an underwater tourism photo object, and can be used as biota indicators of ecosystem health. The purpose of this research is to assess density, diversity index, Evenness index, and dominance index as well as water parameters that support the growth and development of nudibranchs in Humbolt Bay, Jayapura City. The research method used is the Underwater Visual Census (UVC) method at a depth of 5 m and 10 m with an observation width of 2.5 to the right and to the left along 100 m. The results showed that there were 14 types of nudibranchia with 122 individuals, with the dominant species being Phyllidiella pustulosa and Phyllidia varicosa. The density of the nudibranch is quite low, which is around 0.022-0.036 individuals / m2, the Diversity Index is low, which is around 1.228-1.463, the Uniformity Index is classified as a small population, 0.120-0.260 (close to 0), and the Dominance Index is quite stable, namely 0.270-0.402. Based on water parameter data It was found that the waters and habitats in Jayapura City’s Humbolt Bay are under pressure as indicated by the decline in the quality of the ecosystem, but are still in normal conditions that support the growth and development of marine life, especially nudibranchs.